Sublethal Effects of Insecticide Exposure on Megacopta cribraria (Fabricius) Nymphs: Key Biological Traits and Acetylcholinesterase Activity. Issue 1 (25th August 2016) - Miao, Jin; Reisig, Dominic D.; Li, Guoping; Wu, Yuqing
Abstract: Megacopta cribraria F. (Hemiptera: Plataspidae), the kudzu bug, is an invasive insect pest of U.S. soybean. At present, insecticide application is the primary and most effective control option for M. cribraria . In this study, the potential effects of sublethal and low-lethal concentrations (LC10 and LC40 ) of three common insecticides on key biological traits and acetylcholinesterase (AChE) activity of the treated nymphal stage of insect were assessed. The results show that the sublethal concentration of imidacloprid significantly reduced adult emergence rate of M. cribraria . A low-lethal concentration of imidacloprid significantly increased nymphal development time, but significantly decreased adult emergence rate and adult longevity. Both sublethal and low-lethal concentrations of acephate caused an increase in nymphal development time and a reduction in adult emergence rate and adult longevity. Fecundity of females was significantly reduced only by exposure to low-lethal concentrations of acephate. Sublethal and low-lethal concentrations of bifenthrin increased nymphal development time, but significantly decreased adult emergence rate. In addition, we found that the AChE activity of M. cribraria was significantly increased only by LC40 imidacloprid, but strongly inhibited by acephate.